Factors influencing the purchase intention of young consumers towards healthy food products in Malaysia - Mohammad, Mardhiah; Majid, Muhammad; Faizal, Mohamad; Badyalina, Basri; Ramdhan, Nur’ Asyiqin; Mohammad, Noorita (UiTM Press, Universiti Teknologi MARA, 2021)
The incidence of overweight and obesity has shown an increased in the last decade due to improper diet habits and imbalanced intake of healthy food. The situation could be prevented if the young consumers prefer healthy foods. Therefore, this study was aim to explore the relationship of health consciousness, health values and health orientation towards purchase intention of healthy food product in young consumers. Online survey was designed and distributed targeting university students in peninsular of Malaysia. The result of the analysis showed that health values and health orientation indicated a significant relationship to influence the young consumer purchase intention toward healthy food. However, health consciousness showed no significant relationship. In these relations, advertising agencies and policy makers can use these findings explore further the opportunities to cater for this young generation in future.